ALIH KODE DALAM PERGELARAN WAYANG KULIT DI YOGYAKARTA = Codeswitching in Shadow Puppet Performances in Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Studies on codeswitching have been done by previous researchers, however, the focus of investigation in this research is different from those of previous studies. The focus of the investigation is the codeswitching occuring in the performances of the shadow puppet show in Yogyakarta: on several codes being used